Differences between COVID-19-induced acute kidney injury and chronic kidney disease patients - Aroca-Martínez,Gustavo (2022)
Abstract Introduction: This article describes the main differences between COVID-19-induced acute kidney injury (AKI-COVID19) in patients with previous normal renal function (AKI-NRF) and those with chronic kidney disease (AKI-CKD) treated in a high complexity clinic in Barranquilla (Colombia). Material and Methods: The patients included in this study (n: 572) were those with a positive diagnosis of COVID-19 confirmed by detection of a positive PCR for SARS-CoV-2. Of these patients, 188 developed AKI during their hospital stay. Patients’ epidemiological data, serum parameters, and clinical frailty status were recorded. Statistical analysis and comparison among AKI-NRF, AKI-CKD, and non-AKI patients were performed. Results: The incidence of COVID-19-induced AKI was 33%, with the majority classified as AKIN 1, 16% requiring renal replacement therapy, and AKI-COVID19 mortality of 68%. A significantly higher prevalence of hypertension, cardiac disease, and serum reactive C-protein and lower albumin values in AKI-CKD patients was recorded. Mortality rate, invasive ventilation requirement, and D-dimer levels were significantly higher in AKI-NRF patients: Conclusion: Different clinical patterns between AKI-NRF and AKI-CKD were documented.